A dynamic plasmonic manipulation technique assisted by phase modulation of an incident optical vortex beam - Yuan, G. H. (2013)
A novel phase modulation method for dynamic manipulation of surface plasmon polaritons (SPPs) with a phase engineered optical vortex (OV) beam illuminating on nanoslits is experimentally demonstrated. Because of the unique helical phase carried by an OV beam, dynamic control of SPP multiple focusing and standing wave generation is realized by changing the OV beam's topological charge constituent with the help of a liquid-crystal spatial light modulator. Measurement of SPP distributions with near-field scanning optical microscopy showed an excellent agreement with numerical predictions. The proposed phase modulation technique for manipulating SPPs features has seemingly dynamic and reconfigurable advantages, with profound potential for development of SPP coupling, routing, multiplexing and high-resolution imaging devices on plasmonic chips.